A drastic improvement in photocatalytic H-2 production by TiO2 nanosheets grown directly on Ta2O5 substrates - Osuagwu, Benedict; Raza, Waseem; Tesler, Alexander; Schmuki, Patrik (Nanoscale, 2021)
Titanium dioxide (TiO2) is the most frequently studied semiconducting material for photocatalytic water splitting. One of the favored forms of TiO2 for photocatalytic applications is layers of erected single-crystalline anatase nanosheets (NSs), while the most frequently reported substrate used for its synthesis is a fluorine-doped tin oxide (FTO). Herein we demonstrate that anatase TiO2 NS layers can be similarly grown on a Ta2O5 substrate. We found that a Ta2O5 back contact provides a remarkable improvement of the photocatalytic activity of the TiO2 NSs in comparison to a FTO back contact. The TiO2 NSs on Ta2O5 exhibit a 170-fold increase in photocatalytic H-2 production rate than that obtained by TiO2 NSs on FTO substrate. The proposed mechanism reveals that such a drastic enhancement of optimized TiO2 NS arrays on the Ta2O5 substrate is attributed to the blocking nature of Ta2O5 for photo-generated electrons in the TiO2 NSs.
CRIS-Team WoS Importer:2021-07-30